276. Comparison of Ceftaroline in Combination with Either Vancomycin or Daptomycin for the Treatment of Methicillin-resistant Staphylococcus aureus Bacteremia. (31st December 2020) - Welch, Stephanie N; Meredith, Jacqueline; Roshdy, Danya; Medaris, Leigh A; McCurdy, Lewis
Abstract: Background: Recent studies have suggested that combination therapy may be preferred to monotherapy for select patients with methicillin-resistant Staphylococcus aureus bacteremia (MRSA-B); however, direct comparison between various combination regimens is lacking. Methods: This was a multicenter, retrospective cohort study evaluating adult patients with MRSA-B who received vancomycin/ceftaroline (VAN+CPT) or daptomycin/ceftaroline (DAP+CPT) for at least 48 hours between April 1, 2017 and June 30, 2019. Patients with primary respiratory or central nervous system infections were excluded. The primary endpoint was rate of clinical success, defined as survival at 90 days, sterilization of blood cultures within 96 hours of combination therapy initiation, no perceived clinical failure requiring a change in MRSA-active therapy, and absence of recurrence. Secondary endpoints included time to culture clearance from combination therapy initiation, 30-day and in-hospital mortality, adverse events prompting antibiotic discontinuation, and hospital and intensive care unit length of stay. Results: A total of 54 patients were included in the VAN+CPT group and 25 patients in the DAP+CPT group. Baseline characteristics were generally similar between groups, except patients in the VAN+CPT group were younger and more likely to have endocarditis. Bone/joint sources were more common in the DAP+CPT group. Initiation of combination therapy occurred 104.9 hours vs 140.0 hours from index culture collection in the VAN+CPT and DAP+CPT groups, respectively. Rates of clinical success were similar between groups (63.0% vs 64.0%, p=0.93). Time to culture clearance from combination therapy initiation was 50.9 hours in the VAN+CPT group compared to 48.6 hours in DAP+CPT (p=0.83). Rates of nephrotoxicity were higher in those who received VAN+CPT (16.7% vs 0%, p=0.04). Other secondary endpoints were similar between groups. Conclusion: Rates of clinical success were similar between groups, though there was a significantly higher rate of nephrotoxicity noted in the VAN+CPT group. Our study supports that clinical outcomes may be similar between VAN+CPT and DAP+CPT, with greater safety concerns associated with VAN+CPT. Disclosures: All Authors : No reported disclosures